2016
DOI: 10.1111/micc.12291
|View full text |Cite
|
Sign up to set email alerts
|

Early Signs of End‐Organ Damage in Retinal Arterioles in Patients with Type 2 Diabetes Compared to Hypertensive Patients

Abstract: In the early stage of T2DM no hypertrophic remodeling was seen in retinal arterioles. However, hypertrophic remodeling was found in diabetic patients with more than 60 months duration of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Finally, alterations in the vascular extracellular matrix (increased collagen-to-elastin ratio) are observed in the vessel wall of people with T2DM [ 37 ], probably due to inflammatory and pro-fibrotic changes. A recent population-based study reported no difference in wall thickness and cross-sectional area of retinal arterioles between healthy, T2DM and hypertensive subjects at early stages of disease but greater wall thickness in subjects with a diabetes duration of > 60 months compared with other groups, suggesting hypertrophic remodelling in T2DM with advancing disease duration [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, alterations in the vascular extracellular matrix (increased collagen-to-elastin ratio) are observed in the vessel wall of people with T2DM [ 37 ], probably due to inflammatory and pro-fibrotic changes. A recent population-based study reported no difference in wall thickness and cross-sectional area of retinal arterioles between healthy, T2DM and hypertensive subjects at early stages of disease but greater wall thickness in subjects with a diabetes duration of > 60 months compared with other groups, suggesting hypertrophic remodelling in T2DM with advancing disease duration [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…While no significant difference in vessel dimensions were found after the dapagliflozin period compared to baseline, the arteriole wall cross-sectional area and the WLR were both increased after the placebo period. An increased WLR and cross-sectional area are characteristic of the vascular hypertrophy seen in type 2 diabetes [ 31 ]. Our findings may, therefore, indicate a positive effect of the dapagliflozin in preventing microvascular remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with previous data from our study group showing that only patients with long-term T2DM (diabetes duration of >60 month) presented retinal arteriolar hypertrophic remodeling with increased WT compared to healthy individuals and hypertensive patients. [31] Previous data from gluteal arteriolar biopsies indicated hypertrophic arteriolar remodeling, but as previously discussed by our group[31], in these patients no adjustment has been made for potentially important confounding factors such as e.g. age.…”
Section: Discussionmentioning
confidence: 99%